THE EFFECTIVENESS OF THE FAMILY HOPE PROGRAM IN IMPROVING THE STANDARD OF LIVING OF THE COMMUNITY IN KOTA BARU VILLAGE - Syifa Nailah; Dwi Agni Maharani; Imam Mahmud; Damar Wibisono; Usman Raidar (FISIP Universitas Malikussaleh, 2026)
The Family Hope Program is a program carried out by the government designed to reduce poverty levels. This research focuses on analyzing the effectiveness of the Family Hope Program (PKH) in improving the standard of living of the community in Kota Baru Gang Klutum RT 10 Kelurahan. By using a qualitative method with a descriptive approach. Primary data was obtained through in-depth interview sessions with five Beneficiary Families (KPM) of the Family Hope Program (PKH) and the Head of RT 10. In addition, secondary data was collected from relevant previous research journals to strengthen the analysis conducted. And the research findings show that the Family Hope Program (PKH) in Kota Baru Urban Village, Gang Klutum RT 10 Sub-district has provided results that the existence of this program has a great influence in improving economic welfare, and access to education for beneficiary families. Despite the good impact, there are challenges such as quota limitations and inaccurate data collection, which causes some families who should have the right to receive the assistance to not receive it. Therefore, it is necessary to evaluate the data collection system and increase the quota so that the distribution of assistance is more equitable and well-targeted.